IOT Based Smart Irrigation System using Cisco Packet Tracer - Raut, Sanskruti; Motade, Sumitra N (International Journal of Computer Sciences and Engineering, 2021)
Irrigation system is a method used to supply water to the plants as uniformly as possible. In the Internet of Things (IoT), technology devices or sensors are connected via the internet and can be remotely operated and monitored by the user. In this research paper, the implementation is done by performing the simulation for a smart irrigation system with the help of the Cisco packet tracer simulation software with new version Cisco Packet Tracer 7.3.0 (64-bit). This technology can be implemented for developing a smart irrigation system, which consists of devices like a lawn sprinkler, temperature monitor, Humidity monitor, etc., to automate the watering system and remotely monitor the environmental conditions for better growth of the plants. All the devices are connected to the home gateway and can be remotely operated and monitored using a Tablet/PC/Smartphone. Simulation results show that the smart devices such as a sprinkler system and other essential devices for monitoring environmental conditions are connected to the home portal and can be successfully monitored, which helps the farmers/homeowners to grow and maintain plants with ease.